2000
DOI: 10.1359/jbmr.2000.15.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Involvement of the EP4 Subtype of Prostaglandin E Receptor in Osteoclast Formation by Proinflammatory Cytokines and Lipopolysaccharide

Abstract: Prostaglandin E2 (PGE2) exerts its effects through the PGE receptor that consists of four subtypes (EP1, EP2, EP3, and EP4). Osteoclast formation in the coculture of primary osteoblastic cells (POB) and bone marrow cells was enhanced more by 11-deoxy-PGE1 (an EP4 and EP2 agonist) than by butaprost (an EP2 agonist) and other agonists, which suggests that EP4 is the main factor in PGE2-induced osteoclast formation. PGE2-induced osteoclast formation was not observed in the coculture of POB from EP4-deficient (EP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 39 publications
0
32
0
2
Order By: Relevance
“…These factors induce COX-2 expression in osteoblasts, and their induction of osteoclast differentiation is inhibited, at least in part, by aspirin-like drugs; such inhibition is reversed by the addition of PGE 2 , implicating PGE 2 in this process (Tai et al, 1997). Sakuma et al (2000) and Miyaura et al (2000) examined the identity of the EP subtype responsible for mediating this action of PGE 2 . Sakuma et al (2000) found that PGE 2 -induced osteoclast formation was impaired in cocultures of osteoblasts from EP 4 -deficient mice and osteoclast precursors from the spleen of wild-type mice.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors induce COX-2 expression in osteoblasts, and their induction of osteoclast differentiation is inhibited, at least in part, by aspirin-like drugs; such inhibition is reversed by the addition of PGE 2 , implicating PGE 2 in this process (Tai et al, 1997). Sakuma et al (2000) and Miyaura et al (2000) examined the identity of the EP subtype responsible for mediating this action of PGE 2 . Sakuma et al (2000) found that PGE 2 -induced osteoclast formation was impaired in cocultures of osteoblasts from EP 4 -deficient mice and osteoclast precursors from the spleen of wild-type mice.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Sakuma et al (2000) and Miyaura et al (2000) examined the identity of the EP subtype responsible for mediating this action of PGE 2 . Sakuma et al (2000) found that PGE 2 -induced osteoclast formation was impaired in cocultures of osteoblasts from EP 4 -deficient mice and osteoclast precursors from the spleen of wild-type mice. IL-1␤, TNF-␣, and basic fibroblast growth factor also failed to induce osteoclast formation in these cultures.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…The major effect of PGE 2 on resorption is generally considered to occur indirectly via upregulation of RANKL expression and by inhibition of osteoprotegrin expression in osteoblastic cells (Blackwell et al, 2010). It has been suggested that PGE 2 enhances osteoclast formation through EP4 receptor activation on osteoblasts (Mano et al, 2000;Sakuma et al, 2000). Osteoclast formation was enhanced by the presence of an EP4 agonist in coculture of mouse primary osteoblastic cells and bone marrow cells, but not in cocultures of primary osteoblastic cells from EP4 KO mice (Sakuma et al, 2000).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…It has been suggested that PGE 2 enhances osteoclast formation through EP4 receptor activation on osteoblasts (Mano et al, 2000;Sakuma et al, 2000). Osteoclast formation was enhanced by the presence of an EP4 agonist in coculture of mouse primary osteoblastic cells and bone marrow cells, but not in cocultures of primary osteoblastic cells from EP4 KO mice (Sakuma et al, 2000). When osteoblasts are absent, EP4 agonists have an inhibitory effect on osteoclast formation and subsequently on bone resorption (Mano et al, 2000).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…In contrast, EP4 agonist significantly stimulated osteoclastogenesis, while the EP2 agonist showed very little stimulatory response. In addition, another study examined co--cultures of osteoclast precursors with primary osteoblasts, and showed that the expression of EP4 receptors in the primary osteoblasts is crucial to PGE 2 -induced osteoclastogenesis 199 . In identifying the EP receptor involved in PGE 2 -stimulated bone formation, Yoshida et al conducted a seminal study involving both knockout mice and specific EP receptor agonists 200 .…”
Section: Mechanism Of Action On Bonementioning
confidence: 99%